Pulmonary metastases from malignant epithelioid schwannoma of the arm presenting as fast-growing subsolid nodules: Report of an unusual case. (2019) - Borghesi, Andrea; Bercich, Luisa; Michelini, Silvia; Bertagna, Francesco; Scrimieri, Alessandra; Maroldi, Roberto
Abstract: Subsolid pulmonary nodules (SSNs) may be the manifestation of benign and malignant conditions. Malignant SSNs usually correspond to the preinvasive or invasive lepidic growth of pulmonary adenocarcinomas. More rarely, malignant SSNs may be the manifestation of primitive pulmonary lymphomas or metastases from extrapulmonary malignancies. In the case of metastases from extrapulmonary malignancies, the SSNs exhibit more aggressive behavior with rapid growth in a short period of time. The present article describes the first case of pulmonary metastases presenting as fast-growing SSNs in a patient with malignant epithelioid schwannoma of the arm.